Implementing digital signature in .NET-based corporate systems - Sipponen, Tino (My University, 2019)
With the rapidly evolving IT systems the old infrastructures are becoming more and more outdated and cumbersome to use. These systems often consist of multiple different user interfaces, poor user experience and require non-automated and even non-digital activities. However, the functionalities of these systems are still needed. This serves as the main motivation behind this thesis. The scope of this thesis is to introduce one of the many processes in need of digitalization - signing documents, and present ways to implement it into new systems as a digitalized signature process. First, the basics of digital signature is discussed, as well as the options to implement it. Kofax TotalAgility is then presented as the main process engine behind the solution. The practical section includes attempting to transform a collection of existing processes used in the University of Turku into KTA processes, all residing in a single environment. The processes were created in KTA and thus a theoretical solution and a design was found, but the implementation was not accomplished. The conclusion of this thesis is that it is theoretically possible and even recommended to merge the old systems together into a newer systems via different interfaces. This would require a lot of deeper knowledge about all of the connected systems as well as a good architectural solution on how to implement the interfaces and data transfer in general.
Keywords: digital signature, hash algorithm, asymmetric signature algorithm, Kofax TotalAgility, business process